2014
DOI: 10.4314/afrrev.v8i3.13
|View full text |Cite
|
Sign up to set email alerts
|

Towards Utilization of E-Learning in Preparing Business Education Students for the World of Work

Abstract: The study was carried out to determine the perception of Business Studies educators towards the utilization of e-learning in preparing business education students for the world of work. The study was conducted in colleges of education in Anambra state. The population of the study consisted of 80 Business Studies educators in the two colleges of education in the state. Two research questions and two null hypotheses guided the study. A structured questionnaire duly validated by experts was used for data collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The presence of various mobile phone features appears to heighten the intention to use mobile phones. Therefore, this study concurs with other empirical studies, for example, those by Li et al (2012), Ilechukwu (2013) and Nwogu et al (2014), which concluded that the greater the amount of features on a mobile phone, the higher the behavioural intention to utilise that device for various communicating purposes. Uniquely in this study, this happens within a South African TVET setting, a notion which no other studies have explored before.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The presence of various mobile phone features appears to heighten the intention to use mobile phones. Therefore, this study concurs with other empirical studies, for example, those by Li et al (2012), Ilechukwu (2013) and Nwogu et al (2014), which concluded that the greater the amount of features on a mobile phone, the higher the behavioural intention to utilise that device for various communicating purposes. Uniquely in this study, this happens within a South African TVET setting, a notion which no other studies have explored before.…”
Section: Discussionsupporting
confidence: 92%
“…Research indicates that the amount of features on a mobile phone is related to the lifetime of the mobile phone (Li et al 2012). Added to this, empirical evidence shows successful usage or adoption of a technology to be dependent on its full utilisation (Ilechukwu 2013;Nwogu, Udoye & Oguejiofor 2014). In essence, the more features a mobile phone has, the more time the phone may remain in the hands of the user.…”
Section: Mobile Phone Featuresmentioning
confidence: 99%